2003
DOI: 10.1002/pds.760
|View full text |Cite
|
Sign up to set email alerts
|

Refill compliance in type 2 diabetes mellitus: a predictor of switching to insulin therapy?

Abstract: SUMMARYObjective To assess whether switching to insulin therapy in patients with type 2 diabetes mellitus is associated with medication refill compliance of oral hypoglycemic agents. Research Design and Methods The PHARMO Record Linkage System was used as data source for this study. Patients with newly treated type 2 diabetes mellitus were defined as subjects in whom oral hypoglycemic therapy was initiated between 1991 and 1998. We performed a matched case-control study in this cohort. Cases were patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 26 publications
1
22
2
Order By: Relevance
“…15 A study on the systematic review of adherence to medication for diabetes reported that the adherence rate in three retrospective studies ranged from 36 to 93%. [16][17][18] In the present study, 59.5% of the patients reported adherence to an appropriate diet, whereas other studies stated adherence to an appropriate diet as 37-52%. 19,20 Effective self-management is considered the cornerstone of successful diabetes control, and monitoring of blood glucose may have a role in this situation.…”
Section: Discussioncontrasting
confidence: 70%
“…15 A study on the systematic review of adherence to medication for diabetes reported that the adherence rate in three retrospective studies ranged from 36 to 93%. [16][17][18] In the present study, 59.5% of the patients reported adherence to an appropriate diet, whereas other studies stated adherence to an appropriate diet as 37-52%. 19,20 Effective self-management is considered the cornerstone of successful diabetes control, and monitoring of blood glucose may have a role in this situation.…”
Section: Discussioncontrasting
confidence: 70%
“…This could be the result of disease progression or patients' belief that the OHA will cover their insulin lapses. Although Spoelstra et al (27) hypothesized that poor compliance with OHA dosing might lead to use of insulin, the natural progression of the disease complicates that association. Pugh et al (1) noted that generalists and specialists differed in their implementation of practice guidelines.…”
Section: Research Design Andmentioning
confidence: 99%
“…A younger age, 7 a low body mass index, 7 being a woman, 24 taking more than 1 oral antidiabetes drug, 24 an increase in daily dosage frequency or in the number of comedications, 24 and having a history of myocardial infarction, dyslipidemia, depression and atrial fibrillation 25 have all been reported to be predictors of insulin initiation. Researchers in these studies 7,24,25 did not observe factors similar to those that we have identified. These discrepencies may be explained by differences in methodology.…”
Section: Discussionmentioning
confidence: 99%
“…We asked the Régie de l'assurance maladie du Québec to identify all beneficiaries of the drug plan who had received at least 1 prescription of an oral antidiabetes drug between Jan. 1, 1998, and Dec. 24,2004. We defined the index date as the date of the first claim for any oral antidiabetes drug during this period.…”
Section: Inclusion and Exclusion Criteriamentioning
confidence: 99%